COCKNEY AND RECEIVED PRONUNCIATION ACCENTS AS SIGNIFICANT SOCIAL CLASS DETERMINERS IN MY FAIR LADY MOVIE - Sarmi, Ni Nyoman (Faculty of Letters, Dr. Soetomo University, 2016)
This research has main objectives to identify the Cockney and Received Pronunciation accents in My Fair Lady movie spoken by Eliza Doolittle and Professor Henry Higgins. Also, the objective is to find the correlation between the accents and the social backgrounds of both speakers. The result of this research shows that the accents indeed can indicate Eliza and Higgins’ social backgrounds. There are several characteristics that can distinct the Cockney and Received Pronunciation, such as H-dropping, Th- fronting, Diphthong shifting, and G- dropping. Eliza and Henry Higgins speak different accents because they come from different regions in London. Besides, from their accents, it is shown that Eliza with her strong Cockney accent comes from lower class while Henry Higgins with his Received Pronunciation accent comes from upper class. Furthermore, the correlation between accents and social backgrounds is also analyzed in this research. Key Words: Accent, Cockney, Received Pronunciation